Analysis of the Effectiveness of Cooperative Accounting Information Systems with the PIECES Benchmark - Matriansyah, Aldi; Herwiyanti, Eliada (Magister Akuntansi - Universitas Atma Jaya Makassar, 2025)
This study aims to determine the effectiveness of the implementation of the Cooperative accounting information system. The location of the study is the Wastralingga Cooperative, located in Purbalingga, Central Java. The study was conducted by analyzing the workflow and components of the accounting information system before and after the improvement, and analyzing the effectiveness of the accounting information system before and after the improvement. The accounting information system (AIS) used by the Wastralingga Cooperative consists of two main parts: the cooperative financial system and the cooperative commission system. The data used in this study are primary data obtained from interviews and observations, as well as secondary data from documentation. Data were analyzed through reduction, presentation, drawing conclusions, and verification using triangulation techniques and sources. The analysis conducted using the PIECES framework benchmark shows that the Wastralingga AIS is useful in improving the efficiency and accuracy of bookkeeping and financial reporting, but there is still ineffectiveness in the aspect of system security control. Recommendations for improvement for the Wastralingga cooperative accounting information system include documentation standardization, user training, and improving security features. Furthermore, periodic evaluation and maintenance are also needed to ensure optimal system performance. The results of this study provide a contribution in terms of piloting the development of accounting information systems in cooperatives and serve as a reference for further research in line with this.